Antioxidant enzymes activity in embryogenic and non-embryogenic tissues in sugarcane (2014)
The objective of this work was to induce direct somatic embryogenesis from segments of immature leaves of the RB872552 variety of sugarcane and to correlate this morphogenic event with oxidative stress. Two previously described protocols were utilized for the induction of somatic embryogenesis in sugarcane with different supplementations of the culture medium and different incubation conditions. For the conversion of embryos into plants was used MS medium without phytoregulators. Histological analyses and activity of antioxidant enzymes were also conducted for the embryogenic and non-embryogenic tissues. The formation of somatic embryos was obtained in 81 % of the explants with the combination of regulators 2,4-D (2,4-dichlorophenoxyacetic acid)and BAP (6-benzylaminopurine) when incubated under 16 h photoperiod. With regards to the antioxidant enzymes, there was increased activity of peroxidase and an increase in the soluble protein content in embryogenic tissues, whereas lower activities of polyphenol oxidase and catalase appeared in these tissues compared to nonembryogenic tissues. It could be inferred that oxidative stress plays an important role in the induction of somatic embryogenesis in sugarcane.Actividad de enzimas antioxidantes en tejidos embriogénicos yno embriogénicos de caña de azúcarEl objetivo de este trabajo fue inducir la embriogénesis somática directa en segmentos de hojas jóvenes en la variedad de caña de azúcar RB872552, e investigar la correlación de este evento morfogénico con el estrés oxidativo. Se utilizaron dos protocolos de inducción de embriogénesis somática, previamente descritos para caña de azúcar, con distintas suplementaciones en el medio de cultivo y en las condiciones de incubación. Para la conversión de embriones en plantas se utilizó el medio MS sin fitoreguladores. Se realizaron además análisis histológicas y de actividad enzimática antioxidante en tejidos embriogénicos y no embriogénicos. La formación de embriones somáticos ocurrió en 81 % de los explantes, con la combinación de los reguladores de crecimiento 2,4-D (ácido 2,4-diclorofenoxiacético) y BAP (6-bencilaminopurina) e incubación bajo un fotoperiodo de 16 h. Respecto a las enzimas antioxidantes, se observó un incremento en la actividad de peroxidasa y en el contenido de  proteínas solubles en los tejidos embriogénicos, mientras que la polifenoloxidasa y la catalasa presentaron valores más bajos de actividad en estos tejidos, en comparación con los no embriogénicos. Se podría inferir que el estrés oxidativo juega un papel importante en la inducción de la embriogénesis somática en caña de azúcar.